N.N. Ambraseys and C.F.Finkel, The seismicity of Turkey and Adjacent Areas, A historical review - Ζαχαριάδου Ελισάβετ Α. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1997)
[ Δε διατίθεται περίληψη / no abstract available]